Pendidikan Pondok Pesantren Era Revolusi Industri 4.0 - Misnatun, Misnatun (IAIN Takengon, 2022)
This paper discusses Islamic boarding schools in the 4.0 industrial revolution era which have their own characteristics and are different from educational institutions in general. however, along with the changing times (as is the case now in the 4.0 era), Islamic boarding schools have experienced very significant changes and developments. This is done so that Islamic boarding schools graduates can compete with graduates from other public education institutions.